PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS X IPA 1 SMA NEGERI 2 TANJUNG SELOR - SUPRATMAN SUPRATMAN (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2022)
This research is a classroom action research that aims to improve the activities and learning outcomes of mathematics in students of class X IPA 1 SMA Negeri 2 Tanjung Selor through the application of a jigsaw cooperative learning model with a scientific approach. This research was conducted in 2 cycles. Students' mathematics learning outcomes after the first cycle of action were in the "high" category with an average score of 66.93 from the highest score of 88 and the lowest score of 30 from the maximum possible score of 100 with a standard deviation of 12.12. Based on the results obtained, it can be concluded that the results of the research in the first cycle did not meet the indicators to be achieved, thus the research was continued in the second cycle. In cycle II, the activities and learning outcomes of students have increased. The results of observations obtained related to students' mathematics learning activities at the end of cycle II were in the active category. Meanwhile, students' mathematics learning outcomes after the second cycle of action were in the "high" category with an average score of 83.72 from the highest score of 98 and the lowest score of 71 from the maximum possible score of 100 with a standard deviation of 7.52. The results obtained in the second cycle indicate that the success indicators to be achieved have been met. Thus, this research is said to be successful in applying the jigsaw type cooperative learning model with a scientific approach in an effort to improve student learning outcomes. ABSTRAKPenelitian ini adalah penelitian tindakan kelas yang bertujuan untuk meningkatkan aktivitas dan hasil belajar matematika pada peserta didik kelas X IPA 1 SMA Negeri 2 Tanjung Selor melalui penerapan model pembelajaran kooperatif tipe jigsaw dengan pendekatan saintifik. Penelitian ini dilaksanakan sebanyak 2 siklus. Hasil belajar matematika peserta didik setelah tindakan siklus I berada dalam kategori “tinggi” dengan skor rata-rata 66,93 dari skor tertinggi 88 dan skor terendah 30 dari skor maksimum yang mungkin dicapai yaitu 100 dengan standar deviasi 12,12. Berdasarkan hasil yang diperoleh dapat disimpulkan bahwa hasil penelitian pada siklus I belum memenuhi indikator yang ingin dicapai, dengan demikian penelitian dilanjutkan pada siklus II. Pada siklus II, aktivitas dan hasil belajar peserta didik mengalami peningkatan. Hasil observasi yang diperoleh terkait aktivitas belajar matematika peserta didik pada akhir siklus II berada pada kategori aktif. Sementara hasil belajar matematika peserta didik setelah tindakan siklus II berada dalam kategori “tinggi” dengan skor rata-rata 83,72 dari skor tertinggi 98 dan skor terendah 71 dari skor maksimum yang mungkin dicapai yaitu 100 dengan standar deviasi 7,52. Hasil yang telah diperoleh pada siklus II menunjukkan bahwa indikator keberhasilan yang ingin dicapai telah terpenuhi. Dengan demikian, penelitian ini dikatakan berhasil dalam menerapkan model pembelajaran kooperatif tipe jigsaw dengan pendekatan saintifik dalam upaya peningkatan hasil belajar peserta didik.